Variación de la composición química del aceite esencial de hojas de Ishpink (Ocotea quixos) en función del tipo de suelo, el área geográfica, y de factores ambientales dentro de las zonas de cultivo de la especie vegetal, en la región oriental del Ecuador - Carrasco López, Omar Alexander (2016)
Among the secondary metabolites from plant diversity, essential oils are noted for their easy extraction and purification, as well as being potential sources of useful products to domestic and industrial level. The composition of the essential oil of the same plant species can be diverse and dependent of environmental factors associated with development of itself, resulting in different chemotypes, being important to investigate the correlation between essential oil composition and environmental variables of growth plants. Amazon tree cinnamon or Ishpink (Ocotea quixos) is a native plant to the eastern region of Ecuador, its distribution and growth in different environmental conditions can lead to the generation of chemotypes, which may be lost due to deforestation in the area. This study focused on the search and identification of O. quixos chemotypes through the characterization of its leaves’ essential oil composition. It was necessary to make georeferencing of each leaves and soil collected sample and bioclimatic data record. Soil, essential oil composition by GCMS and Multivariate statistical analysis was performed in order to determine whether there is a relationship between environmental factors and essential oil chemical variation. The results show that there is variation in the essential oil chemical composition of several plants collected in different locations, which indicates the existence of chemotypes and therefore a likelihood of association of the composition of essential oil to environmental factors